Product development of Piper retrofractum Vahl candy using value engineering - Khoirul Hidayat; Laha Nuriyana; M Fuad Fauzul Mu’tamar; Muhtadin Muhtadin (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Madura is the largest producer of Piper retrofractum Vahl in Indonesia. However, this commodity has not developed well, so it is necessary to develop Piper retrofractum Vahl candy products and conduct a feasibility study on establishing an agro-industrial factory in Madura. This research aims to develop Piper retrofractum Vahl candy product and feasibility study. The development of the Piper retrofractum Vahl candy product uses the Value Engineering method to produce the best alternative. The best product alternative will be an industrial feasibility analysis that includes analysis of Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Benefit/Cost Ratio (B/C Ratio), and Break Even Point (BEP). The results of this study indicate that there are five attributes in the development of Piper retrofractum vahl candy, namely taste (5), shape (4.3), color (4.3), texture (3.6), and packaging shape (4.3). After conducting an analysis of alternative selection, the best alternative was selected, namely chocolate flavor with a performance value of 3.44, animal shape with a performance value of 5.62, red color with a performance value of 4.9, hard texture (hard candy) with a performance value of 8.04 and transparent packaging shape with a performance value of 8.34. The overall performance value of the best alternative design is 30.34. The results of the financial analysis of the Piper retrofractum Vahl candy product are said to be feasible because its value is above the standard. Thus, the project is economically feasible and can increase the sustainability of Madura local wisdom.